2020
DOI: 10.1016/j.virusres.2020.198025
|View full text |Cite
|
Sign up to set email alerts
|

Porcine sapoviruses: Pathogenesis, epidemiology, genetic diversity, and diagnosis

Abstract: The first porcine Sapovirus (SaV) Cowden strain was discovered in 1980. To date, eight genogroups (GIII, V-IX) and three genogroups (GIII, GV, and GVI) of porcine SaVs have been detected from domestic pigs worldwide and wild boars in Japan, respectively based on the capsid sequences. Although GIII Cowden strain replicated in the villous epithelial cells and caused intestinal lesions in the proximal small intestines (mainly in duodenal and less in jejunum), leading to mild to severe diarrhea, in the orally inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 80 publications
(93 reference statements)
1
19
0
Order By: Relevance
“…Taken together, the association of these several bacteria and viruses with disease pathogenesis as shown by various studies fits well with the clinical signs of disease observed in the herd in this study and could potentially support the role of these identified pathogens for disease pathogenesis [ 26 , 48 , 94 , 133 , 134 ] in which the viral infection might have followed the bacterial infection or vice versa. Despite being a relatively expensive and time intensive technology, in particular for data analysis of even a single sample, NGS has become a powerful tool and has demonstrated numerous advantages over conventional targeted detection technologies by detecting co-infections, novel or unique and emerging pathogens for which detection methods do not exist.…”
Section: Discussionsupporting
confidence: 88%
“…Taken together, the association of these several bacteria and viruses with disease pathogenesis as shown by various studies fits well with the clinical signs of disease observed in the herd in this study and could potentially support the role of these identified pathogens for disease pathogenesis [ 26 , 48 , 94 , 133 , 134 ] in which the viral infection might have followed the bacterial infection or vice versa. Despite being a relatively expensive and time intensive technology, in particular for data analysis of even a single sample, NGS has become a powerful tool and has demonstrated numerous advantages over conventional targeted detection technologies by detecting co-infections, novel or unique and emerging pathogens for which detection methods do not exist.…”
Section: Discussionsupporting
confidence: 88%
“…Among them, 17 genogroups (GII, GIII and GV–GXIX) have been identified in animals and four (GI, GII, GIV and GV) in humans (Scheuer et al., 2013) with genogroups II (GII) and V (GV) detected in both animals and humans (Oka et al., 2015). Thus far, at least eight genogroups (GIII, GV, GVI, GVII, GVIII, GIX, GX, and GXI) of SaVs have been associated with pigs (Nagai et al., 2020; Oka et al., 2016; Scheuer et al., 2013). Our recent genomic characterization study reveals that highly divergent porcine SaV strains co‐circulate in the field in the United States (Wang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine SaV has been identified on every continent except Oceania (Reuter et al, 2010), presenting a wide range of frequency and genotypes. In most of these studies, no direct association was observed between diarrhea and SaV (Reuter et al, 2010;Salamunova et al, 2018;Nagai et al, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Although the viral classification is based on the VP1 gene, Schuffenecker et al (2001) showed that, when comparing different strains of SaVs in the RdRp gene, the 3'ORF and ORF capsid overlapping sequences and 3'UTR (untranslated region) demonstrate the same classification. With this, it is possible to verify that most of the molecular detection studies use the RdRp gene and/or capsid junction region because it presents a more conserved region (Nagai et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation